Pharmacokinetics, bioavailability and metabolism of neferine in rat by LC–MS/MS and LC–HRMS. (1st July 2021) - Hu, Lin; Wang, Yu; Shu, Chang; Yu, Jingjing; Chen, Yueyue; Li, Yali; Tao, Ran; Yang, Huiyuan; Dou, Lei
Abstract: In this study, a simple and sensitive analytical method based on liquid chromatography–tandem mass spectrometry (LC–MS/MS) was developed and validated for the determination of neferine in rat plasma. After acetonitrile‐mediated protein precipitation, the samples were separated on an Acquity BEH C18 column (2.1 × 50 mm, 1.7 μm) maintained at 40°C. The mobile phase comprising 0.1% formic acid in water and acetonitrile was delivered at a flow rate of 0.4 ml/min. The mass detection was conducted using multiple reaction monitoring mode with ion transitions at 625.4 > 206.3 and m/z 622.9 > 380.9 for neferine and internal standard, respectively. The assay was demonstrated to be linear over the concentration range of 0.5–1, 000 ng/ml, with correlation coefficient >0.999 ( r > 0.999). The validated method was further applied to the pharmacokinetic study of neferine in rat plasma. In addition, the metabolism of neferine was investigated using high‐resolution mass spectrometry. A total of six metabolites from rat liver microsomes and plasma were detected and their structures were identified according to their fragment ions. The proposed metabolic pathways of neferine were demethylation, dealkylation, dehydrogenation and glucuronidation.